Genetic control of Fusarium circinatum tolerance in Pinus patula x P. tecunumanii hybrid families - Mphahlele, Lebogang Ivonne (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScFor)--Stellenbosch University, 2020.